A SnOx–brookite TiO2 bilayer electron collector for hysteresis-less high efficiency plastic perovskite solar cells fabricated at low process temperature. Issue 52 (8th June 2016) - Kogo, Atsushi; Ikegami, Masashi; Miyasaka, Tsutomu
Abstract : Thin plastic film-based CH3 NH3 PbI3− x Cl x perovskite solar cells were fabricated at low process temperature using a bilayer comprising an amorphous SnO x and mesoporous brookite TiO2 as electron collectors. Abstract : Thin plastic film-based CH3 NH3 PbI3− x Cl x perovskite solar cells were fabricated at low process temperature using a bilayer comprising an amorphous SnO x and mesoporous brookite TiO2 as electron collectors. Void-less high quality heterojunction structures achieve hysteresis-less photovoltaic performance with a power conversion efficiency as high as 13.4% and mechanical stability against cyclic bending.